Are capital markets efficient? evidence from the term structure of interest rates in Europe - Hughes Hallett, Andrew; Richter, Christian R. (Economic & Social Studies, 2002)
This paper investigates the uncovered interest parity hypothesis in an unusual way. We provide empirical evidence on the efficiency of capital markets using a time domain approach. However, a common prediction from theoretical models is that inefficient capital markets cause greater volatility of the observed time series. By using cross spectral analysis we are able to test this proposition directly. We show, in particular, how this can be done for time-varying models and time-varying spectra. We use our techniques to examine the changing stability of the relationship between British and German interest rates during and following the ERM crisis of 1992/3.
Paper presented at the Sixteenth Annual Conference of the Irish Economic Association
Keywords: Capital markets; Interest rates; Quantitative methods; Europe